STUDENTS' LEARNING DIFFICULTIES IN PROBLEM SOLVING ABILITY IN FACE-TO-FACE LEARNING LIMITED ELEMENTARY SCHOOL - Nuuri Asysyifa Mugnianingsih, Awiria, Zahara Tussoleha Rony (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
Face-to-face learning activities in the current conditions found that there are still students who have difficulty in solving the problem in the topic of shapes. This can be seen from the fact that the success of students in problem solving is still low because students think mathematics is difficult as mathematics is abstract and uses symbols or language. In this study, the researchers wanted to find out more about the types of student learning difficulties in solving questions about shapes and the factors that cause student learning difficulties. This research was conducted using case study research. Collecting data was done to determine students' learning difficulties by using the methods of tests, observations, interviews, and documentation as complementary data in the hope of explaining the types and factors of learning difficulties in problem solving abilities. The results showed that the students had weakness in numeracy, weakness in knowledge, weakness in mathematical language, and visual perception. This is due to the lack of understanding of students' knowledge of mathematical concepts and arithmetic operations, as well as students' lack of accuracy. The factors that cause students to have learning difficulties are giving students negative responses to mathematics lessons, low student motivation, lack of guidance and assistance from family members, and limited time for face-to-face learning.